Passive immunization with equine RBD-specific Fab protects K18-hACE2-mice against Alpha or Beta variants of SARS-CoV-2 - Barbier, Mariette; Lee, Katherine S.; Vikharankar, Mayur S.; Rajpathak, Shriram N.; Kadam, Nandkumar; Wong, Ting Y.; Russ, Brynnan P.; Cyphert, Holly A.; Miller, Olivia A.; Rader, Nathaniel A.; Cooper, Melissa; Kang, Jason; et al. (Frontiers in Immunology, 2022)
Emergence of variants of concern (VOC) during the COVID-19 pandemic has contributed to the decreased efficacy of therapeutic monoclonal antibody treatments for severe cases of SARS-CoV-2 infection. In addition, the cost of creating these therapeutic treatments is high, making their implementation in low- to middle-income countries devastated by the pandemic very difficult. Here, we explored the use of polyclonal F(ab’)2 antibodies generated through the immunization of horses with SARS-CoV-2 WA-1 RBD conjugated to HBsAg nanoparticles as a low-cost therapeutic treatment for severe cases of disease. We determined that the equine F(ab’)2 bind RBD and neutralize ACE2 receptor binding by virus for all VOC strains tested except Omicron. Despite its relatively quick clearance from peripheral circulation, a 100μg dose of F(ab’)2 was able to fully protect mice against severe disease phenotypes following intranasal SARS-CoV-2 challenge with Alpha and Beta variants. F(ab’)2 administration increased survival while subsequently lowering disease scores and viral RNA burden in disease-relevant tissues. No significant improvement in survival outcomes or disease scores was observed in F(ab’)2-treated mice challenged using the Delta variant at 10μg or 100µg doses. Overall, the data presented here provide a proof of concept for the use of F(ab’)2 in the prevention of severe SARS-CoV-2 infections and underscore the need for either variant-specific treatments or variant-independent therapeutics for COVID-19.